If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(k + -6) = 6k + 2 Reorder the terms: 4(-6 + k) = 6k + 2 (-6 * 4 + k * 4) = 6k + 2 (-24 + 4k) = 6k + 2 Reorder the terms: -24 + 4k = 2 + 6k Solving -24 + 4k = 2 + 6k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-6k' to each side of the equation. -24 + 4k + -6k = 2 + 6k + -6k Combine like terms: 4k + -6k = -2k -24 + -2k = 2 + 6k + -6k Combine like terms: 6k + -6k = 0 -24 + -2k = 2 + 0 -24 + -2k = 2 Add '24' to each side of the equation. -24 + 24 + -2k = 2 + 24 Combine like terms: -24 + 24 = 0 0 + -2k = 2 + 24 -2k = 2 + 24 Combine like terms: 2 + 24 = 26 -2k = 26 Divide each side by '-2'. k = -13 Simplifying k = -13
| q+w+y+p+I+12(q+w+11+q+p-11+2345)-qwy=qwypl | | 0.4-0.2=r+4 | | 42=4v+10 | | x+15=x-8 | | 8(19y+7)= | | 7m-2=3m+6 | | .5+3=.50+2 | | -3(1.5+3.2)=1.3 | | -13+3x=-39x+9 | | y=-x^2+x+8 | | 180=96-w | | 5x+10+3x+50=180 | | 216x^6-665x^3-216=0 | | 4(x+6)=4(x+2) | | 5=193-w | | 4.6w+0.19=59.39 | | 17*(-15)= | | -v+152=216 | | 5r-5=2r+11 | | -3x+15-7x=-7 | | 2+3sin(2x)=0 | | 3v-10=20 | | .2x-.08x(x-10)=24.8 | | 18=3x+7 | | 2x-3x-x=-40 | | 6x^2-41x-4=3 | | 82=4y+14 | | 9y-13y+6= | | 6a-4whena=6 | | 3k^2-k-18=6 | | 66+(-81)= | | 75x-2=9x+2 |